Socrates and Arendt: beyond the political framework - Bach, Augusto; Orlandi, Juliano (Faculdade de Filosofia e Ciências, 2020)
In order to understand Arendt’s conceptions of history and political judgment, this article discusses her peculiar interpretation of Socrates. As with her other ideas, such as the banality of evil, the nature of totalitarian terror, and the public space, her portrayal of the Greek philosopher demands that we discriminate between thinking and acting. Would judgment by chance be the bridge between the activities of thought and political action? My aim in this essay is to show how Arendt, from beginning of her work, was looking for an authentic mode of political life, the major example of which is Socrates. I also address what Arendt meant by her idea of a reflexive judgment, an idea that has proved enormously suggestive yet which remains elusive. Recebido: 11/07/2016Aceito: 16/06/2017